Good practices to ensuring the sustainability of trade unions in public institute of higher learning in malaysia - Aziz, Faiq; Ismail, Ismi Arif; Abdullah, Haslinda; Che Nawi, Nur Raihan; Zulkifly, Nurul Afiqah; Audi Azizul, Muhd Dhamir (Human Resource Management Academic Research Society, 2023)
Trade union discussions about sustainable development invariably turn to current social and economic developments, and their implications for workers. Throughout history, workers and their communities have been amongst the first victims of unsustainable patterns of development, whether in the form of job dislocation, community upheaval, industrial disease, or death. In fact, the origins of the union movement itself can be traced to the collective action taken by workers against the atrocious working conditions we now associate with the First Industrial Revolution. Currently, there are 24 trade unions at local institutes of higher learning in Malaysia. Despite recent challenges to their political power in a number of countries, labor unions continue to play an important role in modern societies. It is undeniable that labor unions have retained enough power to be regarded as a determining force in the transition to more sustainable consumption and production patterns. Therefore, this study sought to identify the good practices to ensuring the sustainability of trade unions in public institute of higher learning in Malaysia. A total of 531 union members from 20 local institutes of higher learning in Malaysia involved in this study. Respondents were selected through systematic random sampling technique and the data were collected using online questionnaires. The study showed that the most prominent practices to ensuring the sustainability of trade unions is protecting the welfare and benefits of members, communication channels between employers and employees, and the efficient of union administration. However, respondents contributed the lowest perception in the effective membership management. An effective membership management indicates no significant relationship with practices to ensuring the sustainability of trade unions. In general, labor unions should become more involved in the formulation of sustainable development policies. Given the existing infrastructure, networks, and expertise, increased labor union participation in these processes could significantly contribute to easing potential tensions between competing objectives. Furthermore, a greater involvement of local expertise could help bridge the gap between international policymaking and local implementation.